Development and Validation of RP-HPLC and UV Methods of Analysis for Metribuzin in Its Formulation - Swarna, C.; Babu Naidu, K.; Naidu, N.V.S. (Asian Journal of Chemistry, 2012)
A RP-HPLC and an UV Spectrophotometric assay method were developed and validated for quantitative determination of metribuzin in formulation Tata metri. The chromatography was carried out on a waters symmetry C8 (150 mm × 4.6 m, 5 μm) column with potassium dihydrogen orthophosphate and acetonitrile (60:40 v/v) as mobile phase at 297 nm detector wavelength. The UV method was performed at 297 nm using methanol as solvent. The linearity was established in the range of 2 to 12 μg/mL and 5 to 50 μg/mL for HPLC and UV method respectively. The HPLC method was accurate and precise for the formulation 99.38 to 100.79 %. The UV method also correlated well with HPLC for the analysis of metribuzin in its formulation.